Endo-Periodontal Lesions in Endodontically Treated Teeth with Periapical Pathology - Mihaela Sălceanu; Anca Melian; Cristina Dascălu; Cristian Giuroiu; Corina Concita; Claudiu Topoliceanu; Diana Melian; Andreea Frumuzache; Sorina Mihaela Solomon; Maria-Alexandra Mârţu (Diagnostics, 2025)
Background/Objectives: The aim of this study was to identify and assess the independent risk factors and potential predictors for endo-periodontal lesions (EPLs) in endodontically treated teeth with periapical pathology. Methods: The study group included 90 patients (35 men, 55 women; mean age 47.96 ± 13.495 years) with 126 endodontically treated teeth. Following clinical examinations and radiologic evaluation, 50 patients were diagnosed with endo-periodontal lesions (EPLs) in 64 molars (test group); the control group included 62 endodontically treated teeth without EPLs diagnosed in 40 patients. The independent variables were assessed as risk factors for EPLs. The relationship between patients’ demographic and clinical features and endo-periodontal status was assessed using Chi-squared tests for categorical variables and Student’s t- or Mann–Whitney tests for continuous variables, depending on data distribution. The potential risk factors were characterized by calculating Odds Ratios (ORs) with 95% confidence intervals. The variables included in the multivariate logistic regression model were selected based on their clinical relevance and statistical significance in the univariate analysis. To evaluate the combined effect of the identified risk factors, a binary logistic regression model was constructed using the Enter method. Results: Out of the 126 endodontically treated molars with periapical pathology, 64 teeth (50.8%) were diagnosed with endo-periodontal lesions (EPLs). Patients aged ≥60 years were significantly more represented in the EPL group (32.8%) compared to the control group (12.9%) (p = 0.024). Probing pocket depth ≥ 4 mm was present in 85.9% of teeth with EPLs versus only 30.6% in teeth without EPLs (p < 0.001). Probing pocket depth (PPD) ≥ 4 mm was the strongest predictor (OR = 13.830) and remained significant after adjustment in multivariate analysis (OR = 6.585). PPD ≥ 3.625 mm showed a strong association in univariate analysis (OR = 12.587) and preserved significance in the multivariate model (OR = 6.163). Conclusions: This study highlights age ≥ 60 years and PPD ≥ 4 mm as the most significant independent risk factors for EPLs, emphasizing the need for early periodontal assessment in endodontically treated teeth with periapical pathology. While PPD greater than 3.625 mm is a strong indicator of the presence of EPLs, other factors such as MBL (marginal bone loss) and occlusal considerations appear to have indirect roles in EPL development in endodontically treated teeth with periapical lesions.